Pengaruh Sikap Sosial Dan Kedisiplinan Siswa Terhadap Prestasi Belajar Siswa Kelas Tinggi SDN 4 Monggot Tahun 2015/ 2016 - Sari, Mei Ratna; , Dra. Risminawati, M.Pd (2016)
This research aims to know:(I) the influence of the social attitude towards learning achievements of students, (2) the influence of discipline against students learning achievements of students, (3) influence social attitudes among and discipline against the achievements of the student learning. The population in this research is high grade SDN 4 Monggot numbering 62 students. Samples taken as many as 30 students with techniques Proportionate Stratified Random Sampling. Data collection methods method using question form, observation and documentation. Analytical techniques used were linear regression techniques double, t test, F test, a test of determination, SR (Relative Donations), and SE (Effective Contribution). The results showed (1) there is influence between social attitudes and discipline against the learning achievements of students with a regression equation Y=28,767+0.300X1+0.337 X2, where the influence is shown by their significance Fcount (30.191)>Ftable (2,98), (2) there is the influence of social attitudes towards learning achievements of students demonstrated by tcount (2.961)>ttable (2,056), (3) there is the influence of the discipline the student against student learning achievement demonstrated by tcount (2.56)>ttable (2.056) , (4) social attitudes and discipline among students more dominant variables discipline students. This is shown with the SR Social Attitudes (53,1%)>SR discipline students (46,9%), SE students social Attitude (36,6%) > SE discipline(32,4%).